Diseases of Macroptilium atropurpureum: A review - Lenné, Jillian M.; Sonoda, RM (1985)
Diseases of Macroptilium atropurpureum cv. Siratro caused by fourteen genera of fungi, one bacterium, one virus and one genus of nematodes are described. Rhizoctonia foliar blight, common bean rust, false-rust and leaf-mottling virus are regarded as major constraints to the further use of Siratro in several regions. The latter two diseases have not yet been detected in Australia and care must be taken to prevent their introduction. Resistance to several of the major diseases has been identified, but more screening of existing M. atropurpureum germplasm collections is needed. This should be given a high future priority, especially with respect to multi-institutional collaborative screening in Central and tropical South America where most of these diseases are endemic